Recombinant H7 hemagglutinin expressed in glycoengineered Pichia pastoris forms nanoparticles that protect mice from challenge with H7N9 influenza virus. Issue 50 (25th November 2020) - Liu, Bo; Shi, Pingping; Wang, Tiantian; Zhao, Yongkun; Lu, Shihao; Li, Xiang; Luo, Shiqiang; Chang, Shaohong; Wang, Sha; Sun, Peng; Gong, Xin; Gao, Yuwei; et al.
Highlights: The rH7 was expressed successfully in glycoengineered Pichia pastoris system. The rH7 had complex glycosylation modifications and polymerized to nanoparticles. The 3.75 µg rH7 was found to protect 100% of the mice with 10LD50 of H7N9 strain. Abstract: Cases of H7N9 human infection caused by an avian-origin H7N9 virus emerged in eastern China in 2013, leading to the urgent requirement of developing an effective vaccine to reduce its pandemic potential. In this report, the full-length recombinant H7 protein (rH7) of A/Hangzhou/1/2013 (H7N9) virus was expressed by a glycoengineered Pichia pastoris system. The rH7 protein underwent complex glycosylation modifications and polymerized to nanoparticles of 30–50 nm in diameter. Recombinant H7 (1.9 µg) elicited a > 1:40 hemagglutination inhibition titer, and 3.75 µg rH7 protected 100% of the mice in the mice challenge model with 10-fold 50% lethal dose of the A/Shanghai/2/2013 (H7N9) rat lung-adapted strain. In conclusion, rH7 produced by the glycoengineered P. pastoris can be used for vaccination against the H7N9 virus, and provides an effective platform for the rapid production of future influenza vaccines.